ANALISIS DETERMINAN MINAT BELANJA ONLINE PRODUK TIKTOK SHOP DI KALANGAN MAHASISWA UNIVERSITAS SAMAWA SUMBAWA BESAR - Sutama, I Nyoman; Utami, Gina Tri (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to analyze the determinants of interest in online shopping for TikTok shop products among students at Samawa University, Sumbawa Besar. The type of this study was associative study which aims to determine the effect of product quality, discounts and free shipping on interest in online shopping for Tiktok Shop products among students at Samawa University, Sumbawa Besar. The type of data used in this study was quantitative data obtained directly from research respondents using a questionnaire. The respondents in this study were Samawa University students who had shopped online for Tiktok Shop products, a total of 95 people who were determined using non-probability sampling techniques with the accidental sampling (convenience sampling) method. The data used in this study were processed with SPSS software for analysis using multiple linear regression analysis techniques, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and determinant coefficient testing (R2). The results of this study showed that product quality, discounts and free shipping had a positive and significant effect on interest in online shopping for Tiktok Shop products among Samawa University students, both partially and simultaneously. The degree of effect of product quality, discounts and free shipping on interest in online shopping for Tiktok Shop products among Samawa University students was 60.3%, while the remaining of 39.7% was effected by other variables outside this research model, such as product completeness, shopping comfort, quality information and ease of service.